Reliabilität der Hornhauttomographie nach Implantation von intrakornealen Ringsegmenten bei Keratokonus - Matar, C. (Ophthalmologe, 2020)
BACKGROUND AND OBJECTIVE: Intracorneal ring segments (ICRS) are believed to stop the progression of keratoconus (KC). This statement on progression, however, requires knowledge about measurement reproducibility. The purpose of this study was to compare the reproducibility of tomographic parameters in eyes with KC after femtosecond laser-assisted implantation of INTACS (fs-INTACS) using two different devices and to determine which is more reliable for the follow-up of these patients. PATIENTS AND METHODS: In this study 19 KC eyes were included and repeatedly examined 5 times with the Scheimpflug topography Pentacam HR and the Casia 2 optical coherence tomography (VA-OCT) devices. Outcome measures included the reproducibility and comparability of measurements between the two devices of (1) keratometric refractive power of the anterior cornea and (2) posterior cornea, (3) maximum keratometric refractive power, (4) central corneal thickness and (5) corneal thickness at the thinnest site. RESULTS: The mean differences (Pentacam minus Casia 2) of (1), (2), (3), (4) and (5) were 0.67 dpt, 0.41 dpt, 3.4 dpt, 1.5 µm and 11.8 µm, respectively. The mean SDs of the 5 repeat measurements for (1), (2), (3), (4) and (5) were 0.20 dpt/0.20 dpt, 0.10 dpt/0.07 dpt, 0.75 dpt/0.5 dpt, 6.5 µm/2.4 µm (p = 0.007) and 7.3 µm/1.9 µm (p = 0.001) for Pentacam and Casia 2, respectively. Cronbach’s alpha was better than 0.98 for both devices and all parameters. CONCLUSION: Both Casia 2 and Pentacam enable a reliable assessment of the corneal refractive power in KC after fs-INTACS implantation; however, the reproducibility was significantly better with Casia 2 only for the measurement of corneal thickness. The Pentacam showed significantly higher values for the mean anterior and posterior corneal refractive power and measured significantly thicker at the thinnest point of the cornea compared to Casia 2.